INFLUENCE OF NUTRITIONAL AND ENVIRONMENTAL PARAMETERS ON PHB PRODUCTION BY BACTERIA ISOLATED FROM CONTAMINATED SOILS - KIRAN NEHRA,; NIDHI DAHIYA,; PRIYANKA LATHWAL,; MANPREET SINGH, (International Journal of Pharma and Bio Sciences, 2015)
Polyhydroxybutyrates (PHBs) are an attractive alternative to conventional non-biodegradable plastics, as these have physical properties similar to polypropylene and are also fully biodegradable. In the present study, an attempt was made to isolate efficient PHB producing bacteria from effluent discharge sites of different industries. Using Sudan Black screening method, 20 PHB positive bacteria (PHB yield varying between 12.11 to 82.53 mg/ml) were isolated from contaminated soil samples. Chemical nature of the extracted polymer was confirmed using FTIR analysis. Based upon their biochemical characterization, the isolates were tentatively found to belong to three prominent genera, viz., Bacillus, Staphylococcus and Acinetobacter. Culture medium conditions having glucose as carbon source, ammonium sulphate as nitrogen source, C:N ratio as 20:1, pH at 7.0, and an incubation temperature of 300C were found to support maximum PHB production by all the isolates. At optimized conditions, a few isolates (IBB, ITF and ITG) exhibited significant PHB yields, thus showing a potential for their possible industrial exploitation.